Beliefs, Actual Practices, and Perceptions on the Implementation of 4C Skills Integrated STEM Curriculum in Online Mathematics and Science Learning - Abadi, Abadi; Rahayu, Yuni Sri; Susantini, Endang; Wijayanti, Pradnyo; Hidayah, Rusly (FKIP Universitas Lampung, 2022)
This study tried to find out about beliefs, actual practices, and perceptions of educators and students of the Faculty of Mathematics and Natural Science, Universitas Negeri Surabaya, Indonesia on online education they experienced. The study focused on 4C skills being embedded in STEM curriculum implemented to some courses. The samples were 17 courses including corresponding educators and students who enrolled the courses. Data were collected by observing activities in LMS and synchronous web meeting and by giving questionnaires to the educators and the students. The results informed that educators and students were able to adjust and adapt to online learning with some shortcomings. Educators’ belief that good online courses with 4C skills-integrated STEM curriculum is possible to conduct with some refinements. Students were able to follow courses which include 4C skills with the context of basic STEM knowledge. However, they did not prefer the use of LMS in their learning.Keywords: 4C skills, STEM, online education, mathematics and scienceDOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1751-1758